Boundary-value Problems for Integro-differential Equations of Elliptic Type (Journal of Partial Differential Equations, 1990)
In this paper we study the existence of solutions to the Dirichlet problem for a class of integro-differential equations of elliptic type by using the weakly continuous method.
Keywords: Integro-differential equations; weakty continuous operator; Choquard equation; weak solutions